The Implementation of 21st Century Skills (Communication, Collaboration, Creativity and Critical Thinking) in English Lesson Plan at MTsN 6 Agam - Lathifa Azhary; Ratmanida Ratmanida (Journal of English Language Teaching, 2021)
This research is a descriptive qualitative research. The purpose of this research is to find out how the teacher incorporate 21st century skills (communication, collaboration, creativity and critical thinking skills) in English lesson plan, its implementation in the classroom and problems encountered by the teachers in implementing 21st century skills in the classroom. The research participants was the three civil servant English teachers at MTsN 6 Agam. The instrumentations of this research were lesson plan guide, observation guide and interview guide. This research showed that 21st century skills (communication, collaboration, creativity and critical thinking skills) were incorporated into lesson plans made by the three English teachers. Learning activities were well designed to promote students' ability to communicate, collaborate, be creative and think critically. Meanwhile, 21st century skills were implemented in the classroom; however, the application of collaboration skills had not been fully implemented due to several problems faced by the teacher especially in teaching duration. The other problems were a lack of school facilities, lesson density and students' unfamiliarity towards English subject especially for students’ class VII and VIII.